FAKTOR YANG BERKAITAN TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR MAKANAN DAN MUNUMAN - Rio Irwanto; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The researchhobjectives are aimed at examining the relationship between profitability, capital structure and company growth on firm value in thenfooddand beverage.sub-sector listeddonnthe IDX forrthe 2019-2021 period. The data used in this study are secondary data in quantitative form. The research sample contained in this research was 26 companies. The test used to test the data is the Spearman Rank Correlation test through the SPSS version 25 program. The results of this study indicate that profitability is weakly, positively and significantly related to firmnvalue, capital structure is moderately, negatively and insignificantly related to firm value and firm growth is weakly, negatively and insignificantly related to firm value. The implication of this research is the need for increased earnings managementtin obtaining profits and capital structure management in corporate funding and loans in order to increase firm value.